Sudden death caused by pulmonary fat embolism in a patient with miliary tuberculosis - Katsuya Chinen; Kashima Ito (University of São Paulo, 2019)
An 84-year-old Japanese woman with myelodysplastic syndrome was admitted with pyrexia and dyspnea, but died suddenly during diagnostic evaluation. The autopsy revealed miliary tuberculosis in addition to myelodysplastic syndrome in the bone marrow. The immediate cause of the patient's sudden death was pulmonary fat embolism derived from bone marrow necrosis. This case shows that the infiltration of the myelodysplastic bone marrow by tuberculosis and consequent bone marrow necrosis and fat embolism can be the cause of sudden death. In this article, we report the autopsy results of this unusual cause of sudden death, and discuss tuberculosis-related sudden death with a review of the literature.